Mrs. Stanton's Bible - Kern, Kathi, 1961- (Book collections on Project MUSE., 2001)
Traces the impact of Elizabeth Cady Stanton's religious dissent on the suffrage movement at the turn of the century and presents the first book-length reading of her radical text, the Woman's Bible. Stanton is best remembered for organizing the Seneca Falls convention at which she first called for women's right to vote. Yet she spent the last two decades of her life working for another cause: women's liberation from religious oppression. Stanton came to believe that political enfranchisement was meaningless without the systematic dismantling of the church's stifling authority over women's lives. In 1895, she collaboratively authored this biblical exegesis, just as the women's movement was becoming more conservative. Stanton found herself arguing not only against male clergy members but also against devout female suffragists. Kathi Kern demonstrates that the Woman's Bible itself played a fundamental role in the movement's new conservatism because it sparked Stanton's censure and the elimination of her fellow radicals from the National American Woman Suffrage Association. Mrs. Stanton's Bible dramatically portrays this crucial chapter of women's history and facilitates the understanding of one of the movement's most controversial texts.